A Study on the Understanding of Chemical Compositions of Deposited Fog Water over Central Indo-Gangetic Plain in India - Shahina Raushan Saikh; Md Abu Mushtaque; Sanat Kumar Das (Aerosol and Air Quality Research)
Abstract Fog preserves information about air pollution by pausing air movement and capturing chemical compositions of pollutants into fog droplets. The current study presents a chemical analysis of fog water collected in January 2021 at a rural site, Arthauli, located over the central Indo-Gangetic Plain (IGP) in India. Fog water collected on 11 foggy days during 1st to 21st January 2021, were analyzed for anions (SO42−, Cl−, NO2−, NO3−), and cations (NH4+, Na+, Ca2+, Mg2+, K+) using Ion Chromatography. pH of fog water ranged from 6.4 to 6.8 (Mean = 6.6 ± 0.1), depicting its alkaline nature. Total ionic composition (TIC) comprised majorly of NH4+ (35%), followed SO42− (23%), Ca2+ (15%), Cl− (10%), NO3− (8%), Mg2+ (3%), and Na+, K+, NO2− (2% each). Back-trajectories analysis indicated air movement from western IGP passing over major urban areas before reaching the sampling site. NH4+ had the highest neutralizing factor in fog samples (1.13), followed by Ca2+ (0.48) and Mg2+ (0.07). Analyses from enrichment factors, correlation coefficients, and principal components suggest that NH4+, NO3−, NO2−, SO42−, and Cl− were from anthropogenic sources like agricultural activities, factories, vehicular emissions, brick kilns, thermal plants, fossil fuels combustion, and, biomass burning, while Ca2+, K+, and Mg2+ were from the crustal source from agricultural fields.